SOCIAL REPRESENTATIONS AND AGING: AN INTEGRATIVE REVIEW OF THE LITERATURE - Oliveira, Amanda Maritsa de Magalhães; Lopes, Maria Emília Limeira; Evangelista, Carla Braz; Oliveira, Ana Eloisa Cruz de; Gouvéia, Eloise Maria Lima; Duarte, Marcella Costa Souto (Revista Brasileira de Ciências da Saúde, 2012)
Objective: To investigate themed social representations and aging in scientific publications in the health field. Material and Methods: this is an integrative review of the literature performed in the database Electronic Library Online (SciELO) of the Virtual Library in Health (VLH). The sample consisted of 25 articles available between 2000 and 2011. The descriptor ‘social representations and aging’ was selected for retrieving papers. Results: The analysis of the results was carried out by content analysis technique. In this respect, three thematic categories emerged: (1) Quality of life and health-disease process; (2) social representations about aging, elaborated by elderly members of living together groups; and (3) Care for the elderly people: family-caregivers relationship and institutionalization. Conclusion: The diverse studies have indicated the desire of the elderly in achieving their own autonomy, improving health and quality of life. It is also emphasized the benefits of family ties and care, as well as the overload to which caregivers are subjected. DESCRIPTORES: Social Perception. Aging. Health.